Penggunaan Model Quantum Learning untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas VI SD Negeri 46 Cakranegara - Sari, Komala (MASALIQ, 2023)
The purpose of this study was to find out: To find out that the Quantum Learning model can improve the quality of the listening learning process for class VI students of SD Negeri 46 Cakranegara Odd Semester in the 2022/2023 Academic Year. To find out the Quantum Learning model can improve the quality of listening learning outcomes for class VI students of SD Negeri 46 Cakranegara Odd Semester for the 2022/2023 Academic Year. This research consists of three cycles. The data collection instruments in this study were teacher performance observation sheets, student activity, and evaluation questions at the end of each cycle. Based on the results of the research and discussion, it can be concluded that the use of the quantum learning model with perfected actions in each cycle is proven to be able to improve the quality of the learning process. Improving the quality of this learning process can be seen from the percentage of interest and motivation as well as the activeness of students who have increased from each cycle. In the last cycle that was carried out, namely the third cycle, it was obtained data that students with high interest and motivation were as much as 85.00%. Active students as much as 87.50%. The learning process is said to be of high quality because each indicator reaches a percentage of 85% or more. There is an increase in the quality of Indonesian learning outcomes using the quantum learning model. Improving the learning process causes an increase in the quality of learning outcomes achieved by students. The quality of these results can be seen from the results of students' listening work which has increased from each cycle. In the third cycle, 100% of students scored according to the minimum learning mastery standard (≥ 75). Learning outcomes are said to be of high quality because the percentage of student learning outcomes is more than 85%.